Results of 20-year testing of candidates to synthetic varieties-populations of Scots pine in conditions of Zmiyivske Forestry Enterprise in Kharkiv Region - Tereshchenko, L. I.; Dyshko, V. A. (Forestry and Forest Melioration, 2019)
Introduction Shifting of seed industry to a variety basis is recognized as the final stage of breeding works in Ukraine. According to the Methodology for variety testing of forest woody plants (Patlay & Molotkov 1997) there are two types of varieties-populations, namely a synthetic variety-population originated from a clonal seed orchard (CSO, the 1st or 2nd generations) and a synthetic variety-population originated from a family seed orchard. The results of the study of Scots pine (Pinus sylvestris L.) synthetic population (CSO) progenies have been given in a few papers. Materials and Methods In 1999, we began testing the candidates to Scots pine synthetic varieties-populations simultaneously in Zmiyivske Forest Enterprise and Gutianske Forest Enterprise in Kharkiv Region. Nine CSO populations and one permanent seed production area (PSPA) population from 4 regions have been represented in the variety testing. They were 'Geographical', 'Specific', 'Prykhilky-1', and 'Prykhilky-2' from Kharkiv Region, 'Kyiv-3', 'Kyiv-4' and 'Kyiv-5' from Kyiv Region, 'Kostopil' PSPA from Rivne Region and 'Lutsk-3' and 'Lutsk-2' from Volyn Region. The control variant was the progeny that was grown from the local forest district seeds. Four progenies ('Geographical', 'Prykhilky-1', 'Prykhilky-2', and Kyiv-3) were found to be better than the local control at the age of 20 at Gutianske Forest Enterprise (Dyshko & Torosova 2018). The aim of the work was to analyse the results of the comprehensive evaluation of the candidates to the varieties-populations among 5-year-old and 20-year-old species participating in the variety testing in Zmiyivske Forest Enterprise. The number of verified variant replications was from 2 to 5. The height and diameter of the trees were determined according to standard in mensuration methods (Anuchin 1982). We also defined the condition category (CC) according to the methodology by the UkrRIFFM Selection Laboratory (Volosyanchuk et al. 2003). As for the stem quality, it was assessed depending on how straight it was. To analyse the results, we used the correlation and dispersion analyses. We carried out the evaluation of 4 indicators based on a 5-point scale. To build the scale for estimating the intensity of growth in height and diameter, we used the statistically significant difference between the progenies and the control according to t-criterion. The stem quality was evaluated by such categories as straight, slightly crooked, notably crooked, forks or double trunks. When working on the comprehensive point-based evaluation of the candidates by means of the indices, we took into account how significant or not characteristic it was. Progenies were qualified as potentially productive if they were not less than 2 points different from the control. They were qualified as of little promise if the sum of points they received was 2 and more points less than the control indicator. Results The variety testing showed that livability of 5-year-old Scotch pine trees was 55.4% on average (in the variants it varied from 32 to 74%), livability of 20-year-old Scots pine trees was 46.7% (from 20 to 70%). During 15 years it has decreased by 8.7% only. The plantations were defined as unevenly dense. At the age of 5, the height of the 'Prikhilky-2' progeny was statistically better, and the 'Kyiv-4' progeny grew statistically worse than the control variant. At the same time, 4 out of 10 candidates to the synthetic varieties-populations statistically fell behind it by the diameter. At the age of 20, the 'Geographic' progeny statistically exceeded the control variant in height; none of the progenies exceeded it by the diameter. The progeny 'Lutsk-3' statistically fell behind the control by both growth indices. The 'Geographic', 'Specific' and 'Kyiv-3' progenies were the best by the average tree stem volume. Age correlations (5 and 20 years) of growth rates were insignificant: r = 0.17 (height) and r = 0.12 (diameter). At the age of 5, 70% of plants in plantation had straight trunks (in variants – from 48 to 95%), then, at the age of 20, there were 56% of such trees on the plot (in variants – from 43 to 65%). At the age of 20, progenies from Kharkiv and Kyiv Regions had the highest percentage of trees with the straight trunks. At this age, there were 2.1% of dry trees on the plot, and 7.6% – with the abated growth. The trees of excellent and good condition on the plot made 48% (in variants – from 27 to 62%), which is 21% less than it was at the age of 5. The condition of the variants during that time got somewhat deteriorated. The progeny 'Specific' had the best condition. The results of the comprehensive evaluation of the candidates to variety-populations showed that by the four studied indices, at the age of 5 the progenies of the candidates 'Prikhilky-2' and 'Geographical' from Kharkiv Region were the best, and the 'Kyiv-4' progeny turned to be the worst. At the age of 20, the 'Geographical' progeny was found to be the leader by the sum of the points; the 'Kyiv-3' progeny slightly surpassed the local control. The progeny 'Lutsk-3' got the least points. By the sum of received points, all progenies of the candidates to varieties from Kharkiv and Kyiv Regions did not grow worse than the control variant. Conclusions At the age of 5 and 20, none of 10 candidates to synthetic varieties-populations was statistically superior to the local control by both growth indices. At the age of 20, the 'Lutsk-3' progeny was significantly behind the control variant. Only the 'Geographic' progeny, at the age of 20, had much better growth indices than the control variant. Compared to the trees at 5 years old, at the age of 20 the part of trees with straight stems in the variants decreased by nearly a quarter and varied from 43% to 65%. According to the results of the comprehensive evaluation of the candidates to varieties-populations by the four indices, the 'Prykhylky-2' progeny was qualified as promising at the age of 5 and at the age of 20 – the 'Geographic' progeny. The 'Lutsk-3' progeny turned to be unpromising. In general, progenies from Kharkiv and Kyiv Regions grow at the same level with the local control according to the sum of obtained points. The progenies from Volyn and Rivne Regions showed worse results as compared with the control variant. Further observation of the growth and development of the candidates to synthetic varieties-populations within the variety testing will allow confirming or breaking obtained differentiation by the regions. 3 Figs., 3 Tables, 17 Refs.